La gamificación como estrategia didáctica para el aprendizaje de biología animal con los estudiantes de cuarto semestre de la carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Jimbo Ortiz, Pamela Alexandra (2025)
This research aimed to describe the relevance of gamification as a teaching strategy for learning Animal Biology. It targeted fourth-semester students of the Science Education program (Chemistry and Biology) at the National University of Chimborazo. Students often struggle with complex content when using traditional methodologies. To address this, an interactive digital learning guide titled "The Fascinating World of Vertebrates and Invertebrates" was designed and distributed. It was developed in Genially and used GameBased Learning (GBL). The study used a quantitative, non-experimental, descriptive, and cross-sectional design. Twenty-two university students participated. Results showed considerable increases in motivation, active participation, and understanding of the classification, morphology, and reproduction of vertebrates and invertebrates. Students demonstrated a positive attitude toward the guide, showing interest in interactive activities, visual elements, and challenges. They also recognized the guide's potential to develop cognitive and communicative skills, essential for future teaching. In conclusion, gamification positively supports learning by making it dynamic, motivating, and studentcentered. Its use encourages meaningful, contextually relevant learning, especially for conceptually complex subjects. Continued use in higher education is recommended as an innovative pedagogical strategy. Using digital resources can help strengthen comprehensive academic training.